Strategies of Gender Mainstreaming in Provincial Election of Nepal - Khadka, Gopal (Rupantaran: A Multidisciplinary Journal, 2022)
An election brings changes in society. Both politics and gender emphasize power, prestige, and privileges. The gender gap in politics indicates the level of participation during all aspects of the election. The gender gap in the electoral system proliferates complexity in gender inequality. Gender mainstreaming is a globally accepted means to reduce gender inequality. To examine the status and strategies of gender mainstreaming in provincial level first-past-the-post (FPTP) electoral system, this article is prepared as the title “Strategies of Gender Mainstreaming in Provincial Election of Nepal”. The analysis of this study is based on the report of provincial election published by the election commission, Nepal. A simple and systematic literature review is conducted to collect essential information to fulfill objectives. This study is based on the critical mass theory, critical act approach, and gender mainstreaming approach. There was a low level of gender mainstreaming at the provincial level FPTP electoral system in Nepal. All political parties should formulate and implement an effective strategy at the political level to increase gender mainstreaming in electoral activities. The government of Nepal must implement the Provision of sustainable development goals, the constitution of Nepal, and the international declaration of human rights regarding gender mainstreaming as soon as possible.